2012
DOI: 10.1002/ijc.27551
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence among Nordic airline cabin crew

Abstract: Airline cabin crew are occupationally exposed to cosmic radiation and jet lag with potential disruption of circadian rhythms. This study assesses the influence of work-related factors in cancer incidence of cabin crew members. A cohort of 8,507 female and 1,559 male airline cabin attendants from Finland, Iceland, Norway and Sweden was followed for cancer incidence for a mean follow-up time of 23.6 years through the national cancer registries. Standardized incidence ratios (SIRs) were defined as ratios of obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 45 publications
(91 reference statements)
9
96
2
Order By: Relevance
“…In the only other relatively large study evaluating both exposures (17), breast cancer risk was not associated with cosmic radiation dose after adjusting for parity or with number of flights crossing ≥6 time zones after adjusting for parity and age at first birth. None of the previous studies report evaluating effect modification by parity (17-23).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the only other relatively large study evaluating both exposures (17), breast cancer risk was not associated with cosmic radiation dose after adjusting for parity or with number of flights crossing ≥6 time zones after adjusting for parity and age at first birth. None of the previous studies report evaluating effect modification by parity (17-23).…”
Section: Discussionmentioning
confidence: 85%
“…Studies suggest that flight attendants have an increased incidence of breast cancer compared to the general population (1,2). However, the reason is unclear.…”
mentioning
confidence: 99%
“…An important feature of space weather is the assessment of aircrew exposure due to CR, specifically during GLEs. At present there is no evidence of any immediate threat on human health from SEPs, and the biological risk of radiation doses accumulated by aircrew is still a matter of scientific debate (Sigurdson & Ron 2004;Ballarini et al 2007;Hammer et al 2009;Pukkala et al 2012;Dos Santos Silva et al 2013). In addition, a recent survey of the exposure due to CRs demonstrated that none exceeded the recommended level of 6 mSv/y and the majority of aircrew received around 3 mSv/y (Bennett et al 2013a(Bennett et al , 2013b.…”
Section: Discussionmentioning
confidence: 99%
“…ovary | circadian rhythm | fertility | steroidogenesis D isruption of circadian rhythms has been implicated in a variety of human health conditions, including cancer, diabetes, and infertility (1)(2)(3)(4)(5). Previous work has shown that the brain muscle arnt-like 1 (BMAL1) protein (also known as MOP3 or ARNTL), in a dimeric complex with the CLOCK protein, is an essential component of the "molecular clock" that controls circadian driven gene expression (6,7).…”
Section: −/−mentioning
confidence: 99%